The Influence of Students' Self-Perceptions and Mathematics Experiences on Learning More Mathematics in the Future. (3rd July 2019) - Shih, Jeffrey; Ing, Marsha; Phelan, Julia; Brown, Richard; Maiorca, Cathrine
ABSTRACT: This study explores the relationships among students' perceived learning opportunities in school mathematics, their perceptions of self in mathematics, and their desire to learn more mathematics in the future. Data included student survey responses from eighth and tenth grade students from a state in the Southeast region of the United States. Students were surveyed in the fall (n = 299) and spring (n = 310). The same analyses were replicated at each time point. Results were consistent at each time point and showed that students' desire to learn more mathematics in the future was a function not only of the extent to which they had classroom opportunities, but also whether they developed positive perceptions of themselves in mathematics. This has notable implications for teachers because teachers influence both school mathematics activities and students' sense of self as a mathematics learner.